APLIKASI IRIGASI TETES BERTINGKAT DENGAN PERTANIAN TANAMAN HORTI KULTURA DI PERUMAHAN PADAT PENDUDUK KOTA MATARAM HULU - I DEWA GEDE JAYA NEGARA; BAMBANG HARIYANTO; ANID SUPRIYADI (GANEC SWARA, 2023)
This study aims to determine the effect of the use of 12 mm Netafim (NTF) pipe and ” pvc on a multilevel drip irrigation network, on the ability of irrigation uniformity and irrigation distribution on polybag land. The test was carried out on variations in tower water heights of 220 cm, 120 cm and 30 cm on the lateral drip pipe, data analysis was carried out on irrigation uniformity (CU), and the distribution of irrigation water volume at each network level. The research was conducted on a land area of 1.5 m x 4 m x 2 m, the distance between the irrigation level is 1 m and the tower height is 2.5 m. Based on the results of the analysis, irrigation uniformity was obtained about 95%, with a difference in irrigation volume between levels of about 2 ml – 3 ml in the combination of PVC and NTF, whereas if the drip pipe with NTF alone there was a difference in volume of about 20 ml. With the use of PVC with dripers on the 2nd and 3rd floors, and the use of NTF pipes on the 1st floor, it can improve the shortcomings of the multilevel irrigation system